Determinación de la capacidad de secado de clichés en los secadores eléctricos de la empresa Evolution Flex S.A., 2013. Tecnología de fabricación de un secador híbrido eléctrico-solar para incrementar la eficiencia del sacado de clichés. - Cartagena Alvarado, Miguel Enrique (2014)
In this paper a theoretical and experimental study is carried for the drying of cliches in the Company Evolution Flex SA. Aiming that all cliche material to be dry on the day of production would take place in the shortest possible time, proposing for that as an alternative technology for manufacturing an electric – solar dryer to increase energy efficiency and the production of clichés. Statistical data to analyze the current situation of the drying cliches in the Company is present; data obtained in the experiments conducted by the author in reference to the drying clichés is also shown. Besides presents and analyzes data on solar radiation in Quito. The data obtained allowed to analyze and determine values by calculations for selecting the different materials and their characteristics in order to propose the design of hybrid dryer that meets the demands of the drying process in the Company. To corroborate the proposed cliches dryer, dryer simulation took place by using the ANSYS V15.0 program, where the materials proposed to be constructed were involved.